2009
DOI: 10.1002/mds.22647
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of high‐field MRI for studies in Parkinson's disease

Abstract: Recent advancements in high field magnetic resonance imaging (MRI) technology (3 T and higher), providing increased signal sensitivity and images with more prominent contrasts intrinsic to the brain, offer new opportunities for assessing brain alterations in Parkinson's disease (PD). In this article, the principle benefits of high field MRI for PD research are described and new findings at high magnetic fields are reviewed. Several high field MRI methodologies, including structural MRI, imaging of brain iron, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…Especially DWI appears as a promising candidate since it may detect diffusion abnormalities in the basal ganglia and infratentorial structures in patients with APD even at early disease stages, and is furthermore widely available on whole body MR scanners and acquirable within few minutes. At higher magnetic fields of 3 T and more, several MRI methodologies, including structural MRI, imaging of brain iron, DTI, arterial spin labeling perfusion imaging, rotating frame imaging, and MRS, provide improved sensitivity and image contrasts to study brain alterations in PD [157] . Furthermore, recent fMRI studies have been used to detect preclinical reorganization of functional brain networks with additional recruitment of motor cortical areas in heterozygous Parkin and PINK1 gene mutation carriers [158] , which are at risk to develop PD.…”
Section: Resultsmentioning
confidence: 99%
“…Especially DWI appears as a promising candidate since it may detect diffusion abnormalities in the basal ganglia and infratentorial structures in patients with APD even at early disease stages, and is furthermore widely available on whole body MR scanners and acquirable within few minutes. At higher magnetic fields of 3 T and more, several MRI methodologies, including structural MRI, imaging of brain iron, DTI, arterial spin labeling perfusion imaging, rotating frame imaging, and MRS, provide improved sensitivity and image contrasts to study brain alterations in PD [157] . Furthermore, recent fMRI studies have been used to detect preclinical reorganization of functional brain networks with additional recruitment of motor cortical areas in heterozygous Parkin and PINK1 gene mutation carriers [158] , which are at risk to develop PD.…”
Section: Resultsmentioning
confidence: 99%
“…Early on, Parkinson disease was declared one potential disease group with high benefit from 7 T imaging [42]. In Parkinson disease, SWI imaging at 7 T revealed an increase in susceptibility of the pars compacta compared with controls, which correlates with the predicted increase in brain iron.…”
Section: Vesselsmentioning
confidence: 79%
“…Moreover, MRI studies measuring the width of the SN demonstrated loss of signal in a lateral to medial gradient in PD, correlating with conventional clinical measures of disease severity, but only in a small number of patients. Thus, these results show that morphological changes in PD exist, and, in particular, that the greater sensitivity and higher tissue contrast of MRI at higher magnetic fields may, compared with MRI at lower magnetic fields, lead to stronger and more robust findings of brain atrophy in PD (Schuff, 2006).…”
Section: Mri-based Volumetric Analysismentioning
confidence: 89%